Trade facilitation and social welfare in Africa - Daniel Sakyi; Isaac Bonuedi; Eric Evans Osei Opoku (Journal of African Trade, 2018)
Improving social welfare in the developing world remains a top priority on the global development agenda, as policymakers and international development partners worldwide strive to meet the Sustainable Development Goals by 2030. Using data on 40 African countries over the period 2010-2015, this paper investigates the extent to which trade facilitation contributes to improving social welfare in Africa. To do so, we construct three indices of trade facilitation capturing infrastructure, institutions, and market efficiency from several primary indicators. With regard to social welfare, we use education (net primary school enrollment rate), child health (under-5 mortality rate), population health (life expectancy), and human development (human development index). The system-GMM estimation technique is employed in order to address the problem of endogeneity. The main finding is that better trade facilitation results in improved social welfare outcomes. Our findings suggest that effective trade facilitation reforms, targeted particularly at improving infrastructure, institutions, and market efficiency, will likely be associated with improvements of social welfare in Africa.
Keywords: F13; F14; I30; C33; 330; Trade facilitation; Social welfare; System-GMM; Africa